Israeli history curriculum and the conservative - liberal pendulum. (1st May 2013) - Goldberg, Tsafrir; Gerwin, David
At sixty-four Israel is still a comparatively young nation state, just passing from the 'developing' to the 'developed' phase. It has had five different history curricula for the Jewish 'Mamlakhti' (public non-religious) and the Arab sectors, which account for the majority of the students. For the first five decades the history curriculum did not ignite much controversy. The first curriculum was a rallying curriculum centered on the Jewish national movement and the establishment of Israel. In 1975 an 'academized' curriculum incorporated historical thinking goals – a move away from just an identification stance and towards an analytic stance. The mandatory baccalaureate examination, however, pushed for memorization and coverage. The fourth curriculum in 1993 integrated Jewish and world history with a slightly greater emphasis on world history, covered Israel's first three wars, and historical Jewish Diasporas and ethnicities. One textbook in the late nineties included cases of the deportation of Palestinian civilians during Israel's independence war. The decade since the turn of the millennia has been turbulent and inconsistent. New 'heritage' projects sponsored by right-wing Ministers of Education have alternated with curriculum emphasizing critical thinking, interpretation and multiple sources. The pendulum swung from expressive populist ethnocentricity to critical inquiry and diversity and back. New policies are haphazardly and partially enforced until a rival coalition reaches power and 'debates' curricula by publicizing the attempts to undo or alter them. Little attention was given to the ways teachers or students actually enacted and perceived the curriculum.